TRISUTJI KAMAL'S MUSIC IN FOUR PERIODS - Budianta, Melani (International Review of Humanities Studies, 2021)
This article maps the works of Indonesian female music composer and pianist, Trisutji Kamal, whose career spanned 7 decades. The composer who died in March 2021, was celebrated for the Islamic element of her works. Using the whole oeuvre of her music, personal interviews and historical research, this article argues that the religious element comprises only one period out of the four periods identified in her long career. The article contends that Kamal’s musical style was shaped by European music but tuned into Javanese nuances in its harmony, timbre and dynamic, creating a sense of embellished dissonance. We conclude that this style was brought about by Kamal’s effort in integrating the East and the West, musically as well as culturally. The article fills in the gap in research on Asian composers.